Impyrium - Neff, Henry H. (Neff, Henry H. Impyrium., 2017)
The Faeregine dynasty, which has ruled Impyrium for more than three thousand years, is rising from the ashes after the Cataclysm shook the world. And while the dynasty is on shaky ground, the empress has plans for her youngest, magically talented granddaughter, twelve-year-old Hazel. And when a spy named Hob comes into the palace, he and Hazel form an unlikely bond that could save them both and the entire realm.